Evaluation of spin within abstracts in obesity randomized clinical trials: A cross‐sectional review. Issue 2 (21st December 2018) - Austin, J.; Smith, C.; Natarajan, K.; Som, M.; Wayant, C.; Vassar, M.
Abstract : This is a cross‐sectional analysis of spin in randomized controlled trial (RCT) abstracts published in top‐ranked obesity and general medicine journals. The top seven obesity and four general medicine journals were searched from 1 January 2016 to 31 December 2017. To be included in this study, a trial must be an RCT with non‐significant primary endpoint ( P > 0.05), exclusively randomize subjects with overweight or obesity or have a primary endpoint of weight loss. These studies were analysed by two reviewers for spin in the abstract. The primary endpoint of our investigation was the frequency and type of spin. The secondary endpoint was to assess whether funding source was associated with the presence of spin. Our PubMed search yielded 1143 articles. Primary screening excluded 992 articles, and full‐text evaluation excluded an additional 106. Overall, 45 articles were included. Spin was identified in 21 of the 45 (46.7%) abstracts analysed. Evidence of spin was found in 17 (37.8%) abstract result sections and 11 (24.4%) abstract conclusion sections. Of the 39 RCTs reporting a clinical trial registry, 6 (15.4%) had evidence of selective reporting bias. Our study found that obesity medicine RCTs from top‐ranked journals with non‐significant primary endpoints published in 2016 and 2017 frequently have spin in their abstracts. Abstracts with evidence of spin may influence a reader's perception of new drugs or procedures. These results warrant a careful review of future RCTs, but may not be generalizable to RCTs published in lower‐ranked journals.